The Roadmap for Enhancing University–Industry Research Collaboration in India. (June 2017) - Kumar, Prateek; Gupta, Roopali
In this age of technology-led development and stiff international competition over Intellectual Property Rights (IPRs), developing countries, with their limited financial capabilities, face the challenge of creating appropriate environment that could facilitate the creation and commercialisation of technologies. The recognition of poor scientific outputs as a hindrance to the growth of domestic industry has brought research on the development agenda. This article focuses on university–industry research collaborations as one of the ways to kick-start innovation-led economic growth in India. It explores the evolution of relevant policy paradigm in India and presents the relevant highlights of National IPR Policy 2016. It identifies the impediments in the way of creative university–industry collaborations and offers solutions to attain optimum synergy between the academia and industry.